2003
DOI: 10.1123/jtpe.22.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Gender Appropriateness, Ability, and Competence in Physical Activity

Abstract: Beliefs about gender appropriateness and conceptions of ability have been identified as powerful influences on beliefs about competence. The purpose of this study was to investigate the interaction of those two factors on competence beliefs in physical activity. Participants completed a survey about the sport of hockey, watched a video of a specific hockey skill, and then responded to questions about the skill. Males expressed more confidence in their ability to learn hockey than females, but females who perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 0 publications
2
34
0
6
Order By: Relevance
“…This pattern was in line with previous findings, in which more physically active students scored higher than less active on expectancy beliefs (Xiang, McBride, & Bruene, 2006;Xiang et al, 2003;, and subjective task values in PE (Eccles et al, 1983;Jacobs et al, 2002;. The reason for gender differences in expectancy beliefs and subjective task values may be the result of participation in gender-appropriate activities whereby expectancy beliefs and subjective task values increase as a result (Shen et al, 2003;Solmon et al, 2003). In the present study, the activities undertaken in PE classes such as volleyball, badminton, and floor hockey may be more appropriate for boys.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This pattern was in line with previous findings, in which more physically active students scored higher than less active on expectancy beliefs (Xiang, McBride, & Bruene, 2006;Xiang et al, 2003;, and subjective task values in PE (Eccles et al, 1983;Jacobs et al, 2002;. The reason for gender differences in expectancy beliefs and subjective task values may be the result of participation in gender-appropriate activities whereby expectancy beliefs and subjective task values increase as a result (Shen et al, 2003;Solmon et al, 2003). In the present study, the activities undertaken in PE classes such as volleyball, badminton, and floor hockey may be more appropriate for boys.…”
supporting
confidence: 90%
“…In contrast, gender differences in task values have not been observed in some other studies (Cox & Whaley, 2004;Xiang, McBride, & Bruene, 2006). Several researchers have suggested that differences may be result of participation in gender appropriate activities, when expectancy beliefs increase as a result (Shen et al, 2003;Solmon et al, 2003). Gender differences have, therefore, been found more regularly in gender preference activities, such as dance or ice hockey, as girls and boys will often tend to value activities that they perceive as appropriate for their gender (Gao & Xiang, 2008).…”
Section: Expectancy-value Theorymentioning
confidence: 89%
“…As a result, the image and perception students have would be affected by gender stereotypes, especially in those domains involving a display of features clearly stereotyped as masculine or feminine. As evidenced, these stereotypes usually limit the participation of girls in physical and sport activities [48].…”
Section: Discussionmentioning
confidence: 99%
“…The expectations created by teachers, but also group pressures, could affect the image that boys and girls have of themselves. In the latter case, the construction of an athletic image for a girl could be seen as inappropriate in certain situations [48,52]. Given the social role girls assume, rather than show interest in a task goal orientation, they could be shying away from showing an ego goal orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Li, Harrison, & Solmon, 2004;Solmon et al, 2003). The coding characteristics of all other studies included in the analysis are provided in Table 2.…”
Section: Meta-analysismentioning
confidence: 99%